The Spread of Printing : Western Hemisphere, Greenland - Oldendow, Knud (European History and Culture - Book Archive pre-2000., 1969)
This volume is published as part of the series The Spread of Printing , a history of printing outside Continental Europe and Great Britain. The print edition is available as a set of eleven volumes (9789063000257).